The impact of luxury hotel experience on brand equity and electronic word-of-mouth in Jakarta's hospitality industry - anindya vika; Maria Apsari Sugiat (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study examines the influence of social media marketing activities on brand equity and customer response at Hotel Grand Mercure Jakarta Harmoni. The research investigates how social media marketing activities affect brand awareness and brand image and how these brand equity components impact electronic word-of-mouth (E-WOM) and customer commitment. Using a quantitative approach with data collected from Instagram users through purposive sampling, the study employed Structural Equation Modeling with Partial Least Squares (SEM-PLS) for analysis. Findings reveal that social media marketing activities positively influence brand awareness and image. Furthermore, brand awareness and image significantly affect E-WOM and customer commitment. The research model demonstrates good predictive relevance. These results highlight the strategic importance of effective social media marketing in building brand equity and fostering positive customer responses in the hospitality industry. They give hotel marketers insights to enhance their digital marketing strategies for improved customer engagement and loyalty.